Carbon corrosion properties and performance of multi-walled carbon nanotube support with and without nitrogen-functionalization in fuel cell electrodes. (1st February 2020) - Kanninen, Petri; Eriksson, Björn; Davodi, Fatemeh; Buan, Marthe Emelie Melandsø; Sorsa, Olli; Kallio, Tanja; Lindström, Rakel Wreland
Abstract: Pt-supported on multi-walled carbon nanotubes (MWCNT) and N-modified MWCNT (N-MWCNT) catalysts are synthesized by pyrolysis from emeraldine solution and microemulsion. Their electrochemical properties and carbon corrosion resistance in a Proton Exchange Membrane Fuel Cell (PEMFC) are compared with a commercial Pt/Vulcan catalyst through I–V curves, cyclic voltammetry and CO stripping. The initial fuel cell performances of the Pt/(N-)MWCNT catalysts are superior to Pt/Vulcan. The corrosion of the catalysts is quantified by the continuous measure of the CO2 release by online-mass spectrometry during potentiodynamic cycling between 0.1 and 1.6 V at 80 °C. The results show that Pt/MWCNT (with the lowest double-layer capacity) is the most stable catalyst followed by Pt/N-MWCNT and Pt/Vulcan, initially losing carbon at a rate of 1.1, 3.4 and 4.7 μgC (mg Ctot ) −1 cycle −1, respectively. After about 30% carbon loss (50–70 cycles) all catalysts corrode at an approximate rate of 5.5 μgC mg −1 cycle −1 . At this stage, all show similar electrochemical surface area and double-layer capacity. However, the substantial diminution of the initially very thick and porous Pt/(N-)MWCNT catalyst layers after corrosion consequences in lower fuel cell performance compared to the structurally less affected Pt/Vulcan electrode. The results clearly reveal that CNT-based catalyst supports are more corrosion resistant compared to state-of-the-art Vulcan. Moreover, the performance of the corroded electrodes envisages the importance of electrode porosity.